Semi-solid lithium battery separator and semi-solid lithium battery

By chemically modifying materials such as octavinyl octasesquioxane and cellulose, semi-solid lithium battery separators with excellent ionic conductivity, flame retardant properties and thermal stability are prepared, which solves the insufficient performance of the existing separators The problem has improved the overall performance of the battery.

CN118589144BActive Publication Date: 2024-12-24江西巨电新能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410906805.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2024-12-24
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

The separators of existing semi-solid lithium batteries have low ionic conductivity, which affects the battery's power output and charge and discharge rate, and lacks thermal stability and flame retardant performance.

Method used

Epoxy POSS is prepared by oxidation of octavinyl octassesquioxane by m-chlorperoxybenzoic acid, and then reacted with N,N-dimethylallylamine to produce quaternized POSS, and with 9, 10-dihydro-9-oxa-10-phosphazepin-10-oxide reaction to produce functionalized POSS; at the same time, cellulose is oxidized with sodium periodate and reacted with melamine to form modified cellulose; then Polyamic acid solution, polyvinylpyrrolidone were mixed with functionalized POSS and modified cellulose, and coated and cured to obtain a semi-solid lithium battery separator.

Benefits of technology

It significantly improves the ionic conductivity, flame retardant performance and thermal stability of the semi-solid lithium battery separator, enhances the mechanical properties, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a semi-solid lithium battery separator and a semi-solid lithium battery, and relates to the technical field of battery materials. When preparing the semi-solid lithium battery separator, the present invention oxidizes octavinyl octasilsesquioxane with meta-chloroperbenzoic acid to obtain epoxidized POSS; reacts epoxidized POSS with N,N-dimethylallylamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence to obtain functionalized POSS; cellulose is oxidized with sodium periodate to obtain oxidized cellulose; oxidized cellulose is reacted with melamine to obtain modified cellulose; 4,4'-diaminodiphenyl ether is polycondensed with 3,3',4,4'-biphenyltetracarboxylic dianhydride to obtain a polyamic acid solution; polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose are uniformly mixed, coated and cured to obtain a semi-solid lithium battery separator. The semi-solid lithium battery separator prepared by the present invention has excellent flame retardancy, ionic conductivity, high thermal stability and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a semi-solid lithium battery separator and a semi-solid lithium battery. Background Art

[0002] Semi-solid lithium battery is an emerging lithium-ion battery technology. Compared with traditional liquid lithium battery, it uses solid or gel electrolyte in the electrolyte part, which brings some significant advantages and innovations to the battery. The core of semi-solid lithium battery lies in its electrolyte part. The electrolyte can be solid (such as polymer or ceramic base) or gel (such as polymer gel). This design is aimed at improving the safety of the battery. Solid or gel electrolyte reduces the safety risks of the battery caused by leakage or combustion of liquid electrolyte.

[0003] Semi-solid lithium battery separators also play a key role in the structure of semi-solid lithium batteries. They not only need to isolate the positive and negative electrodes to prevent short circuits, but also must provide sufficient ionic conductivity and mechanical strength to ensure the stability and performance of the battery. Semi-solid lithium separators are slightly inferior to traditional liquid electrolyte battery separators in ionic conductivity, which will affect the power output and charge and discharge rate of the battery. Therefore, inventing a semi-solid lithium battery separator with excellent ionic conductivity and applying it to semi-solid lithium batteries has great potential to improve the comprehensive performance of semi-solid lithium batteries. Summary of the invention

[0004] The object of the present invention is to provide a semi-solid lithium battery separator and a semi-solid lithium battery to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A semi-solid lithium battery separator, characterized in that the semi-solid lithium battery separator is prepared by oxidizing octavinyl octasilsesquioxane with meta-chloroperbenzoic acid to obtain epoxidized POSS; reacting the epoxidized POSS with N,N-dimethylallylamine to obtain quaternized POSS; reacting the quaternized POSS with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain functionalized POSS; oxidizing cellulose with sodium periodate to obtain oxidized cellulose; reacting the oxidized cellulose with melamine to obtain modified cellulose; polycondensing 4,4'-diaminodiphenyl ether with 3,3',4,4'-biphenyltetracarboxylic dianhydride to obtain a polyamic acid solution; and uniformly mixing the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose, and coating and curing the obtained membrane.

[0007] As an optimization, the preparation method of the semi-solid lithium battery separator includes the following preparation steps:

[0008] (1) Epoxidized POSS and toluene were mixed in a mass ratio of 1:(8~10), and N,N-dimethylallylamine solution of 2~3 times the mass of epoxidized POSS was uniformly added dropwise at a stirring rate of 40~50°C and 300~500r / min within 30min, and the reaction was continued with stirring for 2~3h. Under vacuum conditions, it was dried at 50~60°C for 7~8h to obtain quaternized POSS; quaternized POSS, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2~3):(0.03~0.05):(8~10), and the reaction was stirred at 70~80°C and 300~500r / min for 4~5h. Under vacuum conditions, it was dried at 50~60°C for 8~10h to obtain functionalized POSS;

[0009] (2) Mix oxidized cellulose, melamine and N,N-dimethylformamide in a mass ratio of 1:(1.3-1.5):(6-8), stir at 45-55°C and 300-500 r / min for 2-3 h, filter, wash with anhydrous ethanol and deionized water for 3-5 times respectively, and dry at 50-60°C under vacuum for 7-8 h to obtain modified cellulose;

[0010] (3) The polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS and modified cellulose are mixed in a mass ratio of 1:(0.04-0.06):(0.02-0.03):(0.07-0.08), and evenly coated on a glass plate to form a film with a thickness of 12-16 μm. The film is dried at 50-60 °C under vacuum conditions for 4-5 h. The film is removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1-2 h, taken out, and dried at 50-60 °C under vacuum conditions for 8-10 h to obtain a semi-solid lithium battery separator.

[0011] As an optimization, the epoxidized POSS in step (1) is prepared by uniformly mixing octavinyl octasilsesquioxane, meta-chloroperbenzoic acid and chloroform in a mass ratio of 1:(0.03-0.05):(8-10), stirring at 50-60° C. and 300-500 r / min for 3-4 h, and drying at 50-60° C. for 7-8 h under vacuum conditions.

[0012] As an optimization, the N,N-dimethylallylamine solution in step (1) is prepared by uniformly mixing N,N-dimethylallylamine and toluene in a mass ratio of 1:(3-4).

[0013] As an optimization, the oxidized cellulose in step (2) is prepared by uniformly mixing cellulose, sodium periodate and deionized water in a mass ratio of 1:(0.6-0.8):(8-10) under light-proof conditions, stirring at 10-30°C and 300-500 r / min for 2-3 hours, adding ethylene glycol in an amount 2-3 times the mass of sodium periodate, continuing stirring for 20-30 minutes, filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and drying at 50-60°C for 10-12 hours under vacuum conditions.

[0014] As an optimization, the molecular weight of the cellulose is 100,000.

[0015] As an optimization, the polyamic acid solution in step (3) is prepared by uniformly mixing 4,4'-diaminodiphenyl ether and N,N-dimethylformamide in a mass ratio of 1:(6-8) under a nitrogen atmosphere, stirring at 10-30°C and 200-300 r / min for 20-30 min, adding 3,3',4,4'-biphenyltetracarboxylic dianhydride in an amount of 1.2-1.4 times the molar amount of 4,4'-diaminodiphenyl ether, and stirring at 10-30°C and 300-500 r / min for 20-24 h under a nitrogen atmosphere to obtain a polyamic acid solution.

[0016] As an optimization, the model of the polyvinyl pyrrolidone in step (3) is PVP-K30.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] When preparing a semi-solid lithium battery separator, the present invention comprises the following steps: oxidizing octavinyl octasilsesquioxane with meta-chloroperbenzoic acid to obtain epoxidized POSS; reacting epoxidized POSS with N,N-dimethylallylamine to obtain quaternized POSS; reacting quaternized POSS with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain functionalized POSS; oxidizing cellulose with sodium periodate to obtain oxidized cellulose; reacting oxidized cellulose with melamine to obtain modified cellulose; polycondensing 4,4'-diaminodiphenyl ether with 3,3',4,4'-biphenyltetracarboxylic dianhydride to obtain a polyamic acid solution; and uniformly mixing the polyamic acid solution, polyvinyl pyrrolidone, the functionalized POSS and the modified cellulose, and coating and curing the mixture to obtain a semi-solid lithium battery separator.

[0019] Firstly, the carbon-carbon double bond on octavinyloctasilsesquioxane is oxidized into epoxy group by m-chloroperbenzoic acid to obtain epoxidized POSS, and epoxy group is introduced; the epoxy group on epoxidized POSS is reacted with tertiary amine on N,N-dimethylallylamine to obtain quaternized POSS, and quaternary ammonium salt structure and carbon-carbon double bond are introduced; the quaternary ammonium salt structure can improve the ionic conductivity of the semi-solid lithium battery separator, and can also combine with the positive and negative charges of the carboxyl group on the polyamic acid molecular chain to form a cross-linked network, inhibit the relative slip of the molecular chain, and give the semi-solid lithium battery separator excellent mechanical properties; the carbon-carbon double bond on the quaternized POSS is subjected to a phosphine-hydrogen addition reaction with the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to obtain functionalized POSS, and 9,10-dihydro-9-oxa- 10-Phosphophenanthrene-10-oxide; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide contains phosphorus, which can capture free radicals and promote the formation of carbon layers to isolate heat and oxygen, giving the semi-solid lithium battery separator excellent flame retardant properties; functionalized POSS contains a cage-type polysilsesquioxane structure, which is a special structure of organic-inorganic hybrid molecules, consisting of a cage-like core connected by silicon-oxygen bonds and an organic functional group shell connected to the silicon atom. It has a regular cage structure, and the bond energy of the Si-O bond is much higher than the bond energy of the CC bond, so that the functionalized POSS still has good stability under high temperature conditions and is not prone to molecular chain breakage, thereby maintaining good performance under high temperature conditions, giving the semi-solid lithium battery separator excellent thermal stability and flame retardancy.

[0020] Secondly, cellulose is oxidized with sodium periodate to obtain oxidized cellulose, and aldehyde groups are introduced into the oxidized cellulose. The aldehyde groups on the oxidized cellulose react with the amino groups on excess melamine to produce modified cellulose, and triazine structure and amino groups are introduced into the modified cellulose. The triazine structure can generate non-flammable nitrogen-containing gas, absorb heat, dilute oxygen concentration, and further improve the flame retardant properties of the semi-solid lithium battery separator. Cellulose contains a large number of polar groups, has a high affinity with the electrolyte, and has good wettability to the electrolyte. Good wettability between the battery separator and the electrolyte helps to improve the ionic conductivity and enhance the capacity and charge and discharge performance of the battery.

[0021] Finally, 4,4'-diaminodiphenyl ether is polycondensed with an excess of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride to obtain a polyamic acid solution, and the excess of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride is maintained so that both ends of the polyamic acid molecular chain are capped by anhydride groups. The anhydride groups at both ends of the polyamic acid molecular chain can react with the amino groups introduced on the modified cellulose to form a cross-linked network, inhibiting the relative slip of the molecular chains and giving the semi-solid lithium battery separator excellent mechanical properties; polyvinyl pyrrolidone is used as a porogen, and after coating and curing, the polyvinyl pyrrolidone is dissolved in deionized water and removed, so that the semi-solid lithium battery separator has abundant pores, providing more channels for the migration of lithium ions, and further improving the ionic conductivity of the semi-solid lithium battery separator. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] A method for preparing a semi-solid lithium battery separator, the method for preparing a semi-solid lithium battery separator comprising the following preparation steps:

[0024] (1) Octavinyl octasilsesquioxane, m-chloroperbenzoic acid and chloroform were mixed in a mass ratio of 1:0.03:8, stirred at 50°C and 300 r / min for 4 h, and dried at 50°C under vacuum for 8 h to obtain epoxidized POSS; N,N-dimethylallylamine and toluene were mixed in a mass ratio of 1:3 to prepare an N,N-dimethylallylamine solution; epoxidized POSS and toluene were mixed in a mass ratio of 1:8, stirred at 40°C and 300 r / min for 30 min. Add N,N-dimethylallylamine solution twice the mass of epoxidized POSS dropwise at a uniform speed, continue stirring to react for 3 hours, and dry at 50°C for 8 hours under vacuum conditions to obtain quaternized POSS; quaternized POSS, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and N,N-dimethylformamide are uniformly mixed at a mass ratio of 1:2:0.03:8, react at 70°C, 300 r / min, and stir for 5 hours, and dry at 50°C for 10 hours under vacuum conditions to obtain functionalized POSS;

[0025] (2) Under light-proof conditions, cellulose, sodium periodate, and deionized water were mixed in a mass ratio of 1:0.6:8, stirred at 10°C and 300 r / min for 3 h, ethylene glycol twice the mass of sodium periodate was added, stirring was continued for 30 min, filtered, washed with anhydrous ethanol and deionized water 3 times each, and dried at 50°C for 12 h under vacuum conditions to obtain oxidized cellulose; oxidized cellulose, melamine, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.3:6, stirred at 45°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol and deionized water 3 times each, and dried at 50°C for 8 h under vacuum conditions to obtain modified cellulose;

[0026] (3) Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide were mixed at a mass ratio of 1:6, stirred at 10°C and 200 r / min for 30 min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.2 times the molar amount of 4,4'-diaminodiphenyl ether) was added, and the mixture was stirred at 10°C and 300 r / min for 24 h under a nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose were mixed at a mass ratio of 1:0.04:0.02:0.07, and the mixture was evenly coated on a glass plate to form a film with a thickness of 12 μm. The film was dried at 50°C under vacuum for 5 h, removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1 h, taken out, and dried at 50°C under vacuum for 10 h to obtain a semi-solid lithium battery separator.

[0027] A method for preparing a semi-solid lithium battery separator, the method for preparing a semi-solid lithium battery separator comprising the following preparation steps:

[0028] (1) Octavinyl octasilsesquioxane, m-chloroperbenzoic acid and chloroform were mixed in a mass ratio of 1:0.04:9, stirred at 55°C and 400 r / min for 3.5 h, and dried at 55°C for 7.5 h under vacuum conditions to obtain epoxidized POSS; N,N-dimethylallylamine and toluene were mixed in a mass ratio of 1:3.5 to prepare an N,N-dimethylallylamine solution; epoxidized POSS and toluene were mixed in a mass ratio of 1:9, stirred at 45°C and 400 r / min for 30 min. Add N,N-dimethylallylamine solution 2.5 times the mass of epoxidized POSS dropwise at a uniform speed, continue stirring and reacting for 2.5 hours, and dry at 55°C for 7.5 hours under vacuum conditions to obtain quaternized POSS; quaternized POSS, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and N,N-dimethylformamide are uniformly mixed at a mass ratio of 1:2.5:0.04:9, and react at 75°C and 400r / min with stirring for 4.5 hours, and dry at 55°C for 9 hours under vacuum conditions to obtain functionalized POSS;

[0029] (2) Under light-proof conditions, cellulose, sodium periodate, and deionized water were mixed in a mass ratio of 1:0.7:9, stirred at 20°C and 400 r / min for 2.5 h, ethylene glycol (2.5 times the mass of sodium periodate) was added, stirring was continued for 25 min, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C for 11 h under vacuum conditions to obtain oxidized cellulose; oxidized cellulose, melamine, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.4:7, stirred at 50°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C for 7.5 h under vacuum conditions to obtain modified cellulose;

[0030] (3) Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide were mixed at a mass ratio of 1:7, stirred at 20°C and 250 r / min for 25 min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.3 times the molar amount of 4,4'-diaminodiphenyl ether) was added, and the mixture was stirred at 20°C and 400 r / min for 22 h under a nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose were mixed at a mass ratio of 1:0.05:0.025:0.075, and the mixture was evenly coated on a glass plate to form a film with a thickness of 14 μm. The film was dried at 55°C under vacuum for 4.5 h, removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1.5 h, taken out, and dried at 55°C under vacuum for 9 h to obtain a semi-solid lithium battery separator.

[0031] A method for preparing a semi-solid lithium battery separator, the method for preparing a semi-solid lithium battery separator comprising the following preparation steps:

[0032] (1) Octavinyl octasilsesquioxane, m-chloroperbenzoic acid and chloroform were mixed in a mass ratio of 1:0.05:10, stirred at 60°C and 500 r / min for 3 h, and dried at 60°C for 7 h under vacuum conditions to obtain epoxidized POSS; N,N-dimethylallylamine and toluene were mixed in a mass ratio of 1:4 to prepare an N,N-dimethylallylamine solution; epoxidized POSS and toluene were mixed in a mass ratio of 1:10, stirred at 50°C and 500 r / min for 30 min. n, dropwise add N,N-dimethylallylamine solution 3 times the mass of epoxidized POSS at a uniform speed, continue stirring and reacting for 2 hours, and dry at 60°C for 7 hours under vacuum conditions to obtain quaternized POSS; quaternized POSS, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and N,N-dimethylformamide are uniformly mixed at a mass ratio of 1:3:0.05:10, react at 80°C, 500r / min, and stirred for 4 hours, and dried at 60°C for 8 hours under vacuum conditions to obtain functionalized POSS;

[0033] (2) Under light-proof conditions, cellulose, sodium periodate, and deionized water were mixed in a mass ratio of 1:0.8:10, stirred at 30°C and 500 r / min for 2 h, ethylene glycol was added in an amount 3 times the mass of sodium periodate, and stirring was continued for 20 min. The mixture was filtered, washed with anhydrous ethanol and deionized water 5 times each, and dried at 60°C for 10 h under vacuum conditions to obtain oxidized cellulose. Oxidized cellulose, melamine, and N,N-dimethylformamide were mixed in a mass ratio of 1:1.5:8, stirred at 55°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol and deionized water 5 times each, and dried at 60°C for 7 h under vacuum conditions to obtain modified cellulose.

[0034] (3) Under a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide were mixed at a mass ratio of 1:8, stirred at 30°C and 300 r / min for 20 min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.4 times the molar amount of 4,4'-diaminodiphenyl ether) was added, and stirred at 30°C and 500 r / min for 20 h under a nitrogen atmosphere to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose were mixed at a mass ratio of 1:0.06:0.03:0.08, and evenly coated on a glass plate to form a film with a thickness of 16 μm. The film was dried at 60°C under vacuum conditions for 4 h, removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 2 h, taken out, and dried at 60°C under vacuum conditions for 8 h to obtain a semi-solid lithium battery separator.

[0035] Comparative Example 1

[0036] The difference between the preparation method of the semi-solid lithium battery separator of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (3) is modified as follows: in a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:7, stirred at 20°C and 250r / min for 25min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.3 times the molar amount of 4,4'-diaminodiphenyl ether) is added, and stirred at 20°C and 400r / min under a nitrogen atmosphere. The reaction was continued for 22 hours to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, octavinyl octasilsesquioxane, and modified cellulose were mixed uniformly in a mass ratio of 1:0.05:0.025:0.075, and evenly coated on a glass plate to form a film with a thickness of 14 μm, and dried at 55° C. for 4.5 hours under vacuum conditions, and the film was removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1.5 hours, taken out, and dried at 55° C. for 9 hours under vacuum conditions to obtain a semi-solid lithium battery separator. The remaining steps are the same as those in Example 2.

[0037] Comparative Example 2

[0038] The difference between the preparation method of the semi-solid lithium battery separator of Comparative Example 2 and Example 2 is the difference in step (1), and step (1) is modified as follows: octavinyl octasilsesquioxane, meta-chloroperbenzoic acid, and chloroform are mixed uniformly in a mass ratio of 1:0.04:9, stirred at 55°C and 400 r / min for 3.5 hours, and dried at 55°C for 7.5 hours under vacuum conditions to obtain epoxidized POSS; N,N-dimethylallylamine and toluene are mixed uniformly in a mass ratio of 1:3.5 to prepare N,N-dimethylallylamine solution; epoxidized POSS and toluene are mixed uniformly in a mass ratio of 1:9, and N,N-dimethylallylamine solution with a mass of 2.5 times that of epoxidized POSS is uniformly added dropwise at a rate of 30 minutes under stirring conditions of 45°C and 400 r / min, and the stirring reaction is continued for 2.5 hours, and dried at 55°C for 7.5 hours under vacuum conditions to obtain functionalized POSS. The remaining steps are the same as those of Example 2.

[0039] Comparative Example 3

[0040] The preparation method of the semi-solid lithium battery separator of Comparative Example 3 is different from that of Example 2 in that step (1) is not performed, and step (3) is modified as follows: in a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:7, stirred at 20°C and 250 r / min for 25 min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.3 times the molar amount of 4,4'-diaminodiphenyl ether) is added, and stirred at 20°C and 4 00r / min stirring reaction for 22h to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, and modified cellulose are mixed uniformly in a mass ratio of 1:0.05:0.075, and evenly coated on a glass plate to form a film with a thickness of 14μm, and dried at 55°C for 4.5h under vacuum conditions, and the film is removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1.5h, taken out, and dried at 55°C for 9h under vacuum conditions to obtain a semi-solid lithium battery separator. The remaining steps are the same as in Example 2.

[0041] Comparative Example 4

[0042] The preparation method of the semi-solid lithium battery separator of Comparative Example 4 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: in a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:7, stirred at 20°C, 250r / min for 25min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.3 times the molar amount of 4,4'-diaminodiphenyl ether) is added, and stirred at 20°C, 400r / min for 25min. nStirring the reaction for 22 hours to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and cellulose were mixed uniformly in a mass ratio of 1:0.05:0.025:0.075, and evenly coated on a glass plate to form a film with a thickness of 14 μm, and dried at 55° C. for 4.5 hours under vacuum conditions, and the film was removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1.5 hours, taken out, and dried at 55° C. for 9 hours under vacuum conditions to obtain a semi-solid lithium battery separator. The remaining steps are the same as in Example 2.

[0043] Comparative Example 5

[0044] The preparation method of the semi-solid lithium battery separator of Comparative Example 5 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: in a nitrogen atmosphere, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:7, stirred at 20°C and 250 r / min for 25 min, 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.3 times the molar amount of 4,4'-diaminodiphenyl ether) is added, and stirred at 20°C and 40 0r / min stirring reaction for 22h to obtain a polyamic acid solution; the polyamic acid solution, polyvinyl pyrrolidone, and functionalized POSS are mixed uniformly in a mass ratio of 1:0.05:0.025, and evenly coated on a glass plate to form a film with a thickness of 14μm, and dried at 55°C for 4.5h under vacuum conditions, and the film is removed from the glass plate, immersed in deionized water, ultrasonically vibrated for 1.5h, taken out, and dried at 55°C for 9h under vacuum conditions to obtain a semi-solid lithium battery separator. The remaining steps are the same as in Example 2.

[0045] Test Example 1

[0046] Flame retardant performance test

[0047] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 1.

[0048] Table 1

[0049] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 35.78 Comparative Example 1 30.82 Example 2 36.24 Comparative Example 2 31.11 Example 3 36.15 Comparative Example 3 26.58 Comparative Example 4 31.13 Comparative Example 5 30.81

[0050] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the semi-solid lithium battery separator prepared by the present invention has good flame retardant properties.

[0051] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3, indicating that the carbon-carbon double bond on octavinyl octasilsesquioxane is oxidized into an epoxy group by using meta-chloroperbenzoic acid to prepare epoxidized POSS, and an epoxy group is introduced; the epoxy group on the epoxidized POSS is reacted with the tertiary amine on N,N-dimethylallylamine to prepare quaternized POSS, and a carbon-carbon double bond is introduced; the carbon-carbon double bond on the quaternized POSS is subjected to a phosphine-hydrogen addition reaction with the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to prepare functionalized POSS, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is introduced on the functionalized POSS; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is introduced on the functionalized POSS. -10-Phosphaphenanthrene-10-oxide contains phosphorus, which can capture free radicals and promote the formation of carbon layers to isolate heat and oxygen, giving the semi-solid lithium battery separator excellent flame retardant properties; the functionalized POSS contains a cage-type polysilsesquioxane structure, which is a special structure of organic-inorganic hybrid molecules, consisting of a cage-like core formed by silicon-oxygen bonds and an organic functional group shell connected to the silicon atom. It has a regular cage structure, and the bond energy of the Si-O bond is much higher than the bond energy of the CC bond, so that the functionalized POSS still has good stability under high temperature conditions and is not prone to molecular chain breakage, thereby maintaining good performance under high temperature conditions, further improving the flame retardancy of the semi-solid lithium battery separator.

[0052] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 4 to 5, indicating that cellulose is oxidized with sodium periodate to obtain oxidized cellulose, and aldehyde groups are introduced into the oxidized cellulose; the aldehyde groups on the oxidized cellulose react with the amino groups on excess melamine to produce modified cellulose, and a triazine structure is introduced into the modified cellulose; the triazine structure can generate non-flammable nitrogen-containing gas, absorb heat, dilute oxygen concentration, and further improve the flame retardant properties of the semi-solid lithium battery separator.

[0053] Test Example 2

[0054] Thermal stability test

[0055] Test method: The initial decomposition temperature of the embodiment and the comparative example was tested using a thermogravimetric analyzer from NETZSCH, Germany. 10 mg of each embodiment and the comparative example was taken, and the initial decomposition temperature was tested in a nitrogen atmosphere at a heating rate of 20°C / min and a temperature range of 30-900°C to perform thermal stability analysis. The results are shown in Table 2.

[0056] Table 2

[0057] Initial decomposition temperature (℃) Initial decomposition temperature (℃) Example 1 412 Comparative Example 1 406 Example 2 423 Comparative Example 2 401 Example 3 417 Comparative Example 3 325 Comparative Example 4 404 Comparative Example 5 410

[0058] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the semi-solid lithium battery separator prepared by the present invention has good thermal stability.

[0059] By comparison, the initial decomposition temperature of Examples 1 to 3 is greater than the initial decomposition temperature of Comparative Example 3, indicating that the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose are uniformly mixed and coated to obtain a semi-solid lithium battery separator; the functionalized POSS contains a cage-type polysilsesquioxane structure, which is an organic-inorganic hybrid molecule with a special structure, consisting of a cage-like core formed by silicon-oxygen bonds and an organic functional group shell connected to the silicon atom, and has a regular cage structure. The bond energy of the Si-O bond is much higher than the bond energy of the CC bond, so that the functionalized POSS still has good stability under high temperature conditions, and is not prone to molecular chain breakage, thereby maintaining good performance under high temperature conditions, giving the semi-solid lithium battery separator excellent thermal stability.

[0060] Test Example 3

[0061] Ionic conductivity test

[0062] Test method: The ionic conductivity of the embodiments and comparative examples was tested by AC impedance method. The diaphragm was cut into circular samples with a diameter of 18 mm. The positive and negative electrode sheets were replaced with stainless steel to assemble into a blocked type battery (stainless steel sheet / diaphragm / stainless steel sheet). The bulk impedance at 40°C was tested by an electrochemical workstation. The ionic conductivity was calculated according to the formula: ionic conductivity = diaphragm thickness / (bulk resistance × effective contact area) ×%. The results are shown in Table 3.

[0063] Table 3

[0064] Ionic conductivity (mS / cm) Ionic conductivity (mS / cm) Example 1 3.12 Comparative Example 1 2.54 Example 2 3.16 Comparative Example 2 3.05 Example 3 3.07 Comparative Example 3 2.44 Comparative Example 4 3.03 Comparative Example 5 2.39

[0065] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the semi-solid lithium battery separator prepared by the present invention has good ionic conductivity.

[0066] By comparison, the ionic conductivity of Examples 1 to 3 is greater than that of Comparative Examples 1 and 3, indicating that the carbon-carbon double bonds on octavinyloctasilsesquioxane are oxidized into epoxy groups using m-chloroperbenzoic acid to prepare epoxidized POSS, and epoxy groups are introduced; the epoxy groups on the epoxidized POSS are reacted with the tertiary amine on N,N-dimethylallylamine to prepare quaternized POSS, and a quaternary ammonium salt structure is introduced; the quaternary ammonium salt structure can improve the ionic conductivity of the semi-solid lithium battery separator.

[0067] By comparison, the ionic conductivity of Examples 1 to 3 is greater than that of Comparative Example 5, indicating that the polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose are uniformly mixed, coated and cured to obtain a semi-solid lithium battery separator. Cellulose contains a large number of polar groups, has a high affinity with the electrolyte, and has good wettability with the electrolyte. Good wettability between the battery separator and the electrolyte helps to improve the ionic conductivity.

[0068] Test Example 4

[0069] Mechanical properties testing

[0070] Test method: The examples and comparative examples were cut into dumbbell-shaped specimens with a length of 6 mm and a width of 4 mm, and stretched using an electronic universal testing machine at 30°C and a stretching rate of 5 mm / min to test the tensile strength of the specimens. The results are shown in Table 4.

[0071] Table 4

[0072] Tensile strength (MPa) Tensile strength (MPa) Example 1 178.45 Comparative Example 1 151.71 Example 2 182.26 Comparative Example 2 176.91 Example 3 180.63 Comparative Example 3 150.72 Comparative Example 4 147.36 Comparative Example 5 146.24

[0073] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the semi-solid lithium battery separator prepared by the present invention has good mechanical properties.

[0074] Through comparative examples, the tensile strength of Examples 1 to 3 is greater than the tensile strength of Comparative Examples 1 and 3, indicating that the carbon-carbon double bonds on octavinyl octasilsesquioxane are oxidized into epoxy groups using m-chloroperbenzoic acid to prepare epoxidized POSS, and epoxy groups are introduced; the epoxy groups on the epoxidized POSS are reacted with the tertiary amine on N,N-dimethylallylamine to prepare quaternized POSS, and a quaternary ammonium salt structure is introduced; the quaternary ammonium salt structure can combine with the positive and negative charges of the carboxyl groups on the polyamic acid molecular chain to form a cross-linked network, inhibit the relative slip of the molecular chains, and give the semi-solid lithium battery separator excellent mechanical properties.

[0075] Through comparative examples, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 4 to 5, indicating that cellulose is oxidized with sodium periodate to obtain oxidized cellulose, and aldehyde groups are introduced into the oxidized cellulose; the aldehyde groups on the oxidized cellulose react with the amino groups on the excess melamine to obtain modified cellulose, and amino groups are introduced into the modified cellulose; 4,4'-diaminodiphenyl ether is polycondensed with an excess of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride to obtain a polyamic acid solution, and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride is kept in excess so that both ends of the polyamic acid molecular chain are capped with anhydride groups, and the anhydride groups at both ends of the polyamic acid molecular chain can react with the amino groups introduced into the modified cellulose to form a cross-linked network, thereby inhibiting the relative slip of the molecular chains and giving the semi-solid lithium battery separator excellent mechanical properties.

[0076] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A semi-solid lithium battery separator, characterized in that: The preparation method of the semi-solid lithium battery separator comprises the following preparation steps: (1) Epoxidized POSS and toluene were mixed in a mass ratio of 1:(8~10), and N,N-dimethylallylamine solution of 2~3 times the mass of epoxidized POSS was uniformly added dropwise at a stirring rate of 40~50°C and 300~500r / min within 30min, and the reaction was continued with stirring for 2~3h. Under vacuum conditions, it was dried at 50~60°C for 7~8h to obtain quaternized POSS; quaternized POSS, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile, and N,N-dimethylformamide were mixed in a mass ratio of 1:(2~3):(0.03~0.05):(8~10), and the reaction was stirred at 70~80°C and 300~500r / min for 4~5h. Under vacuum conditions, it was dried at 50~60°C for 8~10h to obtain functionalized POSS; (2) Mix oxidized cellulose, melamine and N,N-dimethylformamide in a mass ratio of 1:(1.3-1.5):(6-8), stir at 45-55°C and 300-500 r / min for 2-3 h, filter, wash with anhydrous ethanol and deionized water for 3-5 times respectively, and dry at 50-60°C under vacuum for 7-8 h to obtain modified cellulose; (3) Mixing polyamic acid solution, polyvinyl pyrrolidone, functionalized POSS, and modified cellulose in a mass ratio of 1:(0.04-0.06):(0.02-0.03):(0.07-0.08), uniformly coating the mixture on a glass plate to form a film with a thickness of 12-16 μm, drying the film at 50-60°C for 4-5 h under vacuum conditions, removing the film from the glass plate, immersing the film in deionized water, ultrasonically vibrating the film for 1-2 h, removing the film, and drying the film at 50-60°C for 8-10 h under vacuum conditions to obtain a semi-solid lithium battery separator; The epoxidized POSS in step (1) is prepared by uniformly mixing octavinyl octasilsesquioxane, meta-chloroperbenzoic acid and chloroform in a mass ratio of 1:(0.03-0.05):(8-10), stirring at 50-60° C. and 300-500 r / min for 3-4 hours, and drying at 50-60° C. for 7-8 hours under vacuum conditions.

2. A semi-solid lithium battery separator according to claim 1, characterized in that: The N,N-dimethylallylamine solution in step (1) is prepared by uniformly mixing N,N-dimethylallylamine and toluene in a mass ratio of 1:(3-4).

3. A semi-solid lithium battery separator according to claim 1, characterized in that: The oxidized cellulose in step (2) is prepared by uniformly mixing cellulose, sodium periodate and deionized water in a mass ratio of 1:(0.6-0.8):(8-10) under light-proof conditions, stirring at 10-30°C and 300-500 r / min for 2-3 hours, adding ethylene glycol in an amount 2-3 times the mass of the sodium periodate, continuing stirring for 20-30 minutes, filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and drying at 50-60°C for 10-12 hours under vacuum conditions.

4. A semi-solid lithium battery separator according to claim 3, characterized in that: The molecular weight of the cellulose is 100,000.

5. A semi-solid lithium battery separator according to claim 1, characterized in that: The polyamic acid solution in step (3) is prepared by uniformly mixing 4,4'-diaminodiphenyl ether and N,N-dimethylformamide in a mass ratio of 1:(6-8) under a nitrogen atmosphere, stirring at 10-30° C. and 200-300 r / min for 20-30 min, adding 3,3',4,4'-biphenyltetracarboxylic dianhydride in an amount of 1.2-1.4 times the molar amount of 4,4'-diaminodiphenyl ether, and stirring at 10-30° C. and 300-500 r / min for 20-24 h under a nitrogen atmosphere to obtain a polyamic acid solution.

6. A semi-solid lithium battery separator according to claim 1, characterized in that: The model of the polyvinyl pyrrolidone in step (3) is PVP-K30.

7. A semi-solid lithium battery, wherein the electromagnetic diaphragm of the semi-solid lithium battery is the semi-solid lithium battery diaphragm according to any one of claims 1 to 6.

Citation Information

Cited By

  • Preparation method of solid-state battery diaphragm capable of improving film uniformity

    CN121097343A